PERSEPSI DUKUNGAN ORGANISASI SEBAGAI MEDIATOR HUBUNGAN ANTARA PENGHARGAAN ORGANISASI, KEADILAN PROSEDURAL, DUKUNGAN ATASAN DENGAN KOMITMEN AFEKTIF PADA GURU - Syamsul Hidayat; Ifat Fatimah (Sekolah Tinggi Ilmu Ekonomi AMM, 2019)
This research is to find out the role of Perception Organizational Support (POS) as mediator of the relationship between Organizational Reward (O_R), Procedural Justice (PJ) and Supervisor Support on affective commitment on the teachers in Pondok Pesantren Al-Mubarok, Serang City. A total of 43 teachers were sampled in this study with sampling technique using random sampling. Analysis of data used is Path Analysis with the Lisrel program 8.80. The results of his research indicate that Perceptions of Organizational Support (POS) have been shown to positively mediate between the Organizational Awards and Affective Commitments; Perception Organizational support (POS) has not been proven to influence mediation between Procedural Justice and Affective Commitment; Perceived Organizational Support (POS) has not been shown to have an effect on mediation between Supervisor Support and Affective Commitment; and Perceived Organizational Support (POS) proved to have a positive and significant impact on Affective Commitment. Implications and suggestions are discussed in this study